Grievable Lives during the COVID-19 Pandemic: US-American Television, Melodrama and the Work of Mourning - Nelly Strehlau (Text Matters, 2023)
The present article applies Judith Butler’s notion of “grievable life” to reflect on the manner in which selected US-American television series engaged in the work of mourning and memorializing the loss of life in the first two years of the COVID-19 pandemic, with the aim of noting which lives were deemed “lose-able or injurable” (Butler, Frames 1), and how precarity of life was reflected by fictional narratives that were conceived and produced during the first waves of the pandemic. The article focuses in particular on the way in which network scripted programming operating within the melodramatic convention, namely This Is Us, Grey’s Anatomy and Station 19, incorporated pandemic storylines and which aspects of pandemic reality were highlighted or, conversely, avoided scrutiny.